The Role of Emotions in Mobilization of Society to Fight Climate Change: Constructing Emotional State to Inspire Mass Movement - Mataitytė, Neringa (Politologija, 2021)
How do emotions contribute to mobilizing the international community to join massive protests against climate change? Although it is common to superficially state that protests are full of various emotions, it remains unclear how emotions become collective on the international level and how they ensure the spread of mass mobilization. This research paper examines the process of collectivization of emotions and how it explains mass mobilization in the case of international climate change strikes. This paper raises the question of how the emotional environment was favourably constructed in Greta Thunberg’s case in order to mobilize international society to join climate change strikes, and it aims to reveal how group emotions play an important role in successful international mobilization. Based on Sarah Ahmed’s theory of cultural politics of emotions and James M. Jasper’s theory linking emotions and social movements, it is assumed that specific emotions were circulated to create a distinct emotional environment that inspired the international community to join Thunberg’s climate strike. An Emotional Discourse Analysis revealed that Thunberg’s speeches are full of emotional potential that provokes reactive emotions such as fear, anger and hope in the global society and establishes an injustice-based framing of the problem as well as the dichotomy between the political elite and the global society. This study contributes to the research field of emotions in international relations by exploring in more depth the collectivization of emotions and expands the theory of cultural politics of emotions to include explanations of international politics phenomena such as mass mobilization.
Keywords: emotions; climate change; collectivisation of emotions; emotional discourse; international mobilisation